Giant pressure-enhancement of multiferroicity in CuBr_{2} - J. S. Zhang; Yiqi Xie; X. Q. Liu; A. Razpopov; V. Borisov; C. Wang; J. P. Sun; Y. Cui; J. C. Wang; X. Ren; Hongshan Deng; Xia Yin; et al. (Physical Review Research, 2020)
Type-II multiferroic materials, in which ferroelectric polarization is induced by inversion nonsymmetric magnetic order, promise new and highly efficient multifunctional applications based on the mutual control of magnetic and electric properties. Although this phenomenon has to date been limited to low temperatures, here we report a giant pressure dependence of the multiferroic critical temperature in CuBr_{2}. At 4.5 GPa, T_{C} is enhanced from 73.5 to 162 K, to our knowledge the highest value yet reported for a nonoxide type-II multiferroic. This growth shows no sign of saturating and the dielectric loss remains small under these high pressures. We establish the structure under pressure and demonstrate a 60% increase in the two-magnon Raman energy scale up to 3.6 GPa. First-principles structural and magnetic energy calculations provide a quantitative explanation in terms of dramatically pressure-enhanced interactions between CuBr_{2} chains. These large, pressure-tuned magnetic interactions motivate structural control in cuprous halides as a route to applied high-temperature multiferroicity.